CT-PLANNED transperineal prostate BIOPSY IN patients without a rectum - Gregory S. Merrick (Urology Case Reports, 2020)
A patient at risk of harboring prostate cancer with a history of ulcerative colitis surgically managed with total colectomy (including the distal rectum and anal canal) underwent CT-planned transperineal prostate biopsy with fluoroscopic guidance. We describe the planning and intraoperative technique to obtain prostate biopsy cores.